A randomized controlled trial of nurse follow-up clinics: do they help patients and do they free up consultants' time? - Gradwell, C.; Thomas, K.S.; English, J.S.C.; Williams, H.C. (British journal of dermatology (1951), 2002)
Summary Background Nurse follow‐up clinics have become increasingly popular in recent years. Their impact on service delivery within dermatology may be useful in relation to chronic diseases, where education and treatment concordance are important factors in disease management. Objectives To assess the impact of providing a nurse follow‐up clinic in addition to the normal service provided by the dermatology outpatient department at Queen's Medical Centre, Nottingham, and to obtain pilot data with which to inform future study design. Methods Newly referred patients aged ≥ 14 years and with a diagnosis of either eczema or psoriasis were identified. In a randomized, parallel‐group study with a follow‐up period of 6 weeks, participants were randomized either to normal care, or to receive an additional session with a dermatology nurse specialist immediately after their consultation with the dermatologist. The primary outcome measure was change in quality of life at 6 weeks, as assessed by the Dermatology Life Quality Index (DLQI). Secondary outcomes comprised a comparison of patient knowledge at 6 weeks and the number of consultations (in secondary and primary care) that occurred during the 6‐week follow‐up period. Results Both groups improved by approximately 3 points on the DLQI scale after 6 weeks. The between‐group difference was 0·27 (95% confidence interval − 2·3 to 2·8, P = 0·83). Patients who had seen the nurse were more likely to know how long they should apply treatment (P = 0·05). There was also a marked difference in patients' understanding of how to obtain a repeat prescription (P = 0·01) and from whom they could receive further support (P < 0·001). Following the addition of this service, 33% of follow‐up appointments with a doctor were cancelled in the nurse intervention group. Conclusions Dermatology nurses can add to a dermatology consultation and provide effective patient education and support in managing a skin condition. With this added service nurses could help to free up dermatologists' time, thus allowing them to see more new patients. Cost‐effectiveness studies are now needed.